ON GLOBAL EXISTENCE FOR THE QUASILINEAR WAVE EQUATION WITH BOUNDARY DISSIPATION AND SOURCE TERMS - Cabanillas Lapa, Eugenio (2010)
In this work we are concerned with the existence of strong solutions and exponential decay of the total energy for the initial boundary value problem associated with the quasilinear wave equation with nonlinear source and boundary damping term. The results are proved by means of the potential well method, the multiplier technique and suitable unique continuation theorem for the wave equation with the variable coefficient.